Methodological analysis of didactic construction of information technology disciplines in higher education. (Journal of Educational Sciences, 2016)
Conducted in the article methodological analysis allows to define methodological approaches to identification of essence of the concept of didactic construction of IT-disciplines and to build its system-active model. Among the General scientific approaches the author identifies systemic, holistic, activity-related and praxiological approaches. Specifically,research (didactic) approaches in the study are personality-activity, competence and technology. These approaches also provide a theoretical basis and tools for construction didactic objectives, content and technologies of teaching IT-disciplines. The author of the levels: philosophical, General scientific, concrete science and technology illustrated the constructionof a course on information technology training. The proposed stages of construction disciplines: clarifying the goals of a discipline; definition of psychological-pedagogical and organizational-pedagogical conditions of teaching; clarification of the structure and content of the IT-disciplines; the definition of pedagogical technologies of learning; structuring and meaning of the content; selection (development) of training and methodological support; selection (development) of methods and means of diagnostics;the reflexive stage.
Keywords: construction; discipline; methodology; pedagogy; construction educational; the construction of the course